A high-profile thread with grit-blasted and acid-etched surface reduces loosening of medial column fusion bolt in instable Charcot foot. Issue 6 (August 2020) - Mehlhorn, Alexander T.; Ugland, Karl I.; Hörterer, Hubert; Gottschalk, Oliver; Südkamp, Norbert; Walther, Markus
Highlights: Bony consolidation of fusion sites is improved using surface modified medial column fusion bolt in Charcot foot. Despite an initial restoration of the foot arch in both groups loss of correction was seen in controls only. Frequency of adverse events like bolt dislocation and bolt breakage was reduced. Abstract: Background: Intramedullary fusion bolts (FB) were introduced to stabilize the medial column of the instable Charcot foot (ICF), but complications as bolt loosening or breakage are frequent. We compared the use of a standard FB and a high-profile threaded FB with a grit-blasted surface. We hypothesized that implant related complications occurred less often and osseous consolidation of fusion sites was more distinctive using the latter type of FB. Methods: Consecutive patients suffering from an ICF were stabilized with a high-profile threaded and surface-modified FB (HTFB) (n = 20) or with a standard FB (n = 20) which was placed into the first ray. Additional bolts and dorsal low-profile plates were applied in every patient. In a retrospective assessment osseous consolidation of the fusion sites was analyzed at 3 month and quantified by CT scan. At 3 and 12 month longitudinal foot arch collapse and rate of bolt loosening were assessed. Results: Compared to the control group, the HTFB group reached significant higher consolidation after 3 month. No dislocation and a single bolt breakage was observed in the HTFB group after the fourth month, while the control group included 3 patients with bolt dislocation at 3 ± 1 month and 5 patients with bolt breakage at 6 ± 1.8 month. Compared to preoperative values, the improvement of Meary's angle after one-year was significant higher in the HTFB group (23.4° ± 14) than in controls (11.7° ± 13). Conclusions: Modification of bolt design improves the stability of the medial column: A higher rate of osseous consolidation of the medial column leads to lower rate of bolt dislocation/breakage and finally to permanently erected longitudinal foot arch. Initially disappointing results following medial column stabilization with fusion bolts can be rejected by modifications of bolt design and its technical application.